Decolonizing the theatre space a conversation - Hodge-Dallaway, Simeilia; Kwei-Armah, Kwame; Poglio-Nwabali, Olivia (London Methuen Drama, 2024)
"2020 was a year in which global politics radically shifted, catalyzed by the Covid-19 pandemic and the #BlackLivesMatter movement. This book is a response to that year, asking was it a moment or is it a movement and what fundamental changes within the arts industry need to come out of this time? The book includes 20 interviews with some of the most pioneering black cultural leaders from a wide range of senior executive positions in the arts within the UK, US and Africa. It documents the sea of change in arts leadership post the height of the#Blacklivesmatter movement, the pressure on organisations to confront and change their racial and ethnic make-up, and shines a light on the guiding ambitions, strategic plans and visions for the future to support the ongoing decolonization of arts organisations across the world. Learn from those who have walked the walk to support your vision for the future" --Provided by publisher.
Includes bibliographical references and index.
AL-2502 donated by UP DSCTA
Keywords: Art and social action; Decolonization in art; Arts -- Management; Black people -- Employment